Hippocampal GABA enables inhibitory control over unwanted thoughts - Taylor W. Schmitz (Nature Portfolio, 2017)
It is not fully understood how intrusive or unwanted memories are regulated. Here the authors show that hippocampal GABA concentrations, and coupling between the dorsolateral prefrontal cortex and hippocampus, predict how well subjects can suppress unwanted memories when presented with a reminder.